2000
DOI: 10.1095/biolreprod63.5.1567
|View full text |Cite
|
Sign up to set email alerts
|

Selective Protein Kinase C Isoforms Are Involved in Endothelin-1-Induced Human Uterine Contraction at the End of Pregnancy

Abstract: The role of protein kinase C (PKC) in contraction of the human myometrium induced by endothelin-1 (ET-1) was investigated at the end of pregnancy. The expression and subcellular distribution of PKC isoforms were examined by Western blot analysis using isoform-specific antibodies. At least three conventional PKC isoforms (cPKC; alpha, beta1, and beta2), two novel PKC isoforms (epsilon and delta), and an atypical PKC isoform (zeta) were detected in pregnant myometrium. Quantitative immunoblotting revealed that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 34 publications
(38 reference statements)
0
23
1
Order By: Relevance
“…In the human myometrium, it has been reported that the PKC isozyme distribution is different between the nonpregnant and the pregnant myometrium (Hurd et al 2000), and that agonist-induced contraction is mediated by PKC isozyme activation (Eude et al 2000). Recently, we have found that PKC activation, especially PKCb activation, stimulated the activation processes of the smooth muscle contractile element in the human myometrium, and that the expression of PKCb in the pregnant myometrium was significantly increased at the late stage of pregnancy (37-40 weeks of gestation) when compared with that in the nonpregnant myometrium (Ozaki et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In the human myometrium, it has been reported that the PKC isozyme distribution is different between the nonpregnant and the pregnant myometrium (Hurd et al 2000), and that agonist-induced contraction is mediated by PKC isozyme activation (Eude et al 2000). Recently, we have found that PKC activation, especially PKCb activation, stimulated the activation processes of the smooth muscle contractile element in the human myometrium, and that the expression of PKCb in the pregnant myometrium was significantly increased at the late stage of pregnancy (37-40 weeks of gestation) when compared with that in the nonpregnant myometrium (Ozaki et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…HSCs have properties similar to vascular smooth muscle cells [29]. Some authors contend that PKC-d and PKC-z are necessary for ET-1 induced myometrial contraction [31] whereas others suggest that there is a role for PKC-1 as a regulator of smooth muscle contraction [32]. Dessy et al implicate PKC-a in myogenic contractions of the coronary microcirculation [33].…”
Section: Discussionmentioning
confidence: 99%
“…We showed that exposure to PMA for 24 h downregulated DAG-sensitive PKCs but not atypical PKC-. Although Calphostin C competitively inhibits binding at the DAG and the phorbol ester-binding site, several studies have shown Calphostin C can also inhibit the function of PKC- (55)(56)(57)(58). Previous reports suggest that MC PKC-may be activated in HG (26) and that activation of ERK1/2 in HG (without agonist) is inhibited by Calphostin C (32,59).…”
Section: Discussionmentioning
confidence: 99%